Organic Pollutant Degradation Through Photocatalysis: Progress, Challenges, and Sustainable Solutions (Mini Review) - Sak, Gamze; Tasar, Seyda; Dursun, Gulbeyi (Mdpi, 2025)
The rapid increase in global population and industrial activities has intensified the discharge of toxic organic pollutants-including antibiotics, dyes, phenolic compounds, and pesticides-into the environment, posing critical threats to both ecosystems and human health. Conventional treatment technologies remain largely inadequate for their complete removal, particularly for pollutants with complex structures and high persistence. Among advanced approaches, photocatalytic systems have emerged as a sustainable and environmentally friendly technology, capable of mineralizing organic pollutants into harmless end products. However, their large-scale application is hindered by inherent limitations such as restricted visible-light activity, low quantum efficiency, and rapid recombination of charge carriers. This mini-review critically examines recent advances aimed at overcoming these bottlenecks, including band gap engineering, metal and non-metal doping, and the incorporation of carbon-based nanomaterials (e.g., CNTs, GO, CQDs). Special emphasis is placed on strategies that enhance photocatalytic activity under visible light, as well as the emerging potential of waste-derived carbon-based photocatalysts for sustainable applications. Finally, key research gaps-such as scalability, long-term stability, and techno-economic feasibility-are discussed to provide future perspectives on the rational design of next-generation photocatalysts.
Keywords: photocatalytic systems; organic pollutants; photocatalysts; carbon-based materials; purification technologies